Advanced ovarian pregnancy: an elusive diagnosis - ., Bhanupriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Primary ovarian ectopic is a rare variant of ectopic pregnancies. It is commonly confused with tubal pregnancy aborted over ovary, hemorrhagic ovarian cyst, ruptured corpus luteal cyst. The women with ovarian ectopic generally presents early because of early onset hemorrhage in ovary. This is a rare case where woman with ectopic pregnancy presents at 13 weeks. The clinical picture is also highly unusual with just spotting and fainting attacks at the end of first trimester to make a diagnosis of ectopic pregnancy. The laparotomy done showed an unruptured ovarian ectopic pregnancy and with 350 cc hemoperitoneum. Salpingoopherectomy was done and the ectopic mass was removed as hardly any ovarian tissue was left to conserve the ovary. Hence, clinicians should be cautious enough to keep a differential diagnosis of ectopic even at advanced gestation.